Intermittent hypoxic–hyperoxic training on cognitive performance in geriatric patients. Issue 1 (9th February 2017) - Bayer, Urike; Likar, Rudolf; Pinter, Georg; Stettner, Haro; Demschar, Susanne; Trummer, Brigitte; Neuwersch, Stefan; Glazachev, Oleg; Burtscher, Martin
Abstract: Introduction: Intermittent hypoxic–hyperoxic training (IHHT) may complement a multimodal training intervention (MTI) for improving cognitive function and exercise tolerance in geriatric patients. Methods: Thirty‐four patients (64–92 years) participated in this randomized controlled trial. Before and after the 5‐ to 7‐week intervention period (MTI + IHHT vs. MTI + ambient air), cognitive function was assessed by the Dementia‐Detection Test (DemTect) and the Sunderland Clock‐Drawing Test (CDT), and functional exercise capacity by the total distance of the 6‐Minute Walk Test (6MWT). Results: DemTect and CDT indicated significantly larger improvements after MTI + IHHT (+16.7% vs. −0.39%, P < .001) and (+10.7% vs. −8%, P = .031) which was also true for the 6MWT (+24.1% vs. +10.8%, P = .021). Discussion: IHHT turned out to be easily applicable to and well tolerated by geriatric patients up to 92 years. IHHT contributed significantly to improvements in cognitive function and functional exercise capacity in geriatric patients performing MTI.